Insulin resistance in the course of acne – literature review - Sadowska-Przytocka, Anna; Gruszczyńska, Michalina; Ostałowska, Anna; Antosik, Patrycja; Czarnecka-Operacz, Magdalena; Adamski, Zygmunt; Łącka, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Acne vulgaris is a very common skin disease being diagnosed in Westernized populations, however, its multifactorial etiopathogenesis still remains unclear. Recent research has demonstrated a possible linkage between acne and insulin resistance (IR), which is the topic of our review. In addition to an inappropriate diet, excessive androgen production or obesity, it is the IR which might be responsible for lack of efficacy of classical treatment strategy in acne. Interestingly, in all such cases an increased activity of mammalian target of rapamycin kinase complex 1 (mTORC1) has been detected. This observation might be considered as the basis of the possible role of metformin as an adjunct therapeutic modality for patients suffering from acne. The aim of our review is to present the possible etiological correlation between acne and insulin resistance, as well as metformin therapy, which might be highly useful in the treatment to resistant forms of acne.